A Multiplicity Result for a Singular and Nonhomogeneous Elliptic Problem in Rn (Journal of Partial Differential Equations, 2012)
We establish sufficient conditions under which the quasilinear equation  $$-div(|∇u|^{n-2}∇u)+V(x)|u|^{n-2}u=\frac{f(x,u)}{|x|^β}+εh(x) in \mathbb{R}^n,$$ has at least two nontrivial weak solutions in $W^{1,n} (\mathbb{R}^n)$ when ε > 0 is small enough, 0≤β < n, V is a continuous potential, f(x,u) behaves like $exp{γ|u|^{n/(n-1)}}$ as $|u|→∞$ for some γ > 0 and h≢ 0 belongs to the dual space of $W^{1,n} (\mathbb{R}^n)$.
Keywords: Moser-Trudinger inequality; exponential growth